2011
DOI: 10.1152/ajplung.00114.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatide-activated type II NKT cells prevent allergic airway inflammation by inhibiting type I NKT cell function in a mouse model of asthma

Abstract: Asthma is a common chronic inflammatory disease involving many different cell types. Recently, type I natural killer T (NKT) cells have been demonstrated to play a crucial role in the development of asthma. However, the roles of type II NKT cells in asthma have not been investigated before. Interestingly, type I and type II NKT cells have been shown to have opposing roles in antitumor immunity, antiparasite immunity, and autoimmunity. We hypothesized that sulfatide-activated type II NKT cells could prevent all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 29 publications
(44 reference statements)
3
39
0
Order By: Relevance
“…However more functional studies are needed in humans to clarify their pathogenic role in asthma. Consistent with a regulatory role for type II NKT cells, a recent study in a murine model of asthma has shown that activation of type II NKT cells by sulfatide or their adoptive transfer results in reduced inflammatory cellular infiltrate in the lung and decreased levels of IL-4/IL-5 and antigenreactive IgE in the lung [104]. Additionally similar to other experimental models, this is associated with the inactivation of type I NKT cells following sulfatide administration.…”
Section: Nkt Cells In Pathogenesis Of Asthmasupporting
confidence: 60%
“…However more functional studies are needed in humans to clarify their pathogenic role in asthma. Consistent with a regulatory role for type II NKT cells, a recent study in a murine model of asthma has shown that activation of type II NKT cells by sulfatide or their adoptive transfer results in reduced inflammatory cellular infiltrate in the lung and decreased levels of IL-4/IL-5 and antigenreactive IgE in the lung [104]. Additionally similar to other experimental models, this is associated with the inactivation of type I NKT cells following sulfatide administration.…”
Section: Nkt Cells In Pathogenesis Of Asthmasupporting
confidence: 60%
“…NKT cells are a heterogeneous population with type I NKT cells being most abundant and best characterized while the rest being type II NKT cells (35). The role of type II NKT cells remains largely unknown due to the lack of specific analytical tools, although some studies have suggested that a subset of type II NKT cells with reactivity to glycolipid sulfatides may have opposing functions to type I counterparts in some experimental settings such as autoimmunity, liver injury, and asthma (35)(36)(37). The role of type II NKT cells in adipose tissue in the context of obesity remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Although showing a relatively diverse TCR repertoire, type II NKT cells share similar phenotypic and functional features with iNKT cells, including high autoreactivity (Gumperz et al 2000; Brigl et al 2006), PLZF-dependent development (Zhao et al 2014), and rapid secretion of a wide range of cytokines after stimulation (Zhao et al 2014). Many diverse NKT cells show an activated or memory phenotype, consistent to the rapid activation and secretion of cytokines (Zhang et al 2011). Diverse NKT cells appear to be more abundant in humans than invariant NKT cells, as shown with CD1d tetramer or dimer staining (Chang et al 2008; Nair et al 2015).…”
Section: Diverse Nkt Cellsmentioning
confidence: 99%